User behavior and energy efficiency in north cyprus university dormitories: a case study - Eslamnoor, Nikan; Vural, S. Müjdem (Journal of housing and the built environment, 2022)
Recent studies present the fact that technological advancements and improvements in building physical elements are not sufficient on their own to achieve the desired energy performance. Real-life practice-based studies not only confirm this fact, but show that the efficiency performance results do not meet the expectations of simulations and theoretical studies. An aspect that influences this situation and unpredictability is occupant behavior and user interactions with building elements. The objective of this study is to shed light on some of these human behaviors that influence the energy performance of buildings, particularly student accommodation buildings, which have rarely been discussed in terms of energy efficiency and user behavior. For this purpose, this study reviews recent publications in the fields of energy efficiency and user behavior in relation to energy use. Then, two student dormitories at Eastern Mediterranean University were selected for investigations. The investigations took the forms of direct observation and questionnaire survey with the aim to identify the user behaviours influencing energy use in these buildings. The results show the existence of wasteful behavioral patterns in both dormitory buildings. Nevertheless, these inefficiencies can be reversed by informative and retrofitting actions. It is necessary for dormitories and universities to have a clear vision of the overall behavioral patterns of students and the existing opportunities for improvement for future planning.